Experimental study for the properties of Fe3O4 dusty plasma using the air in vacuum chamber system - Ahmed, Ala’ Fadhil (Iraqi Journal of Physics, 2019)
In this work, we carried out an experimental study of thedusty plasma by taking the dust material Fe3O4 with radius of the any grain 0.1μm - 0.5μm. In experiment we use air in the vacuum chamber system under different low pressure (0.1-1) Torr. The results illustrated that the present of dust particles in the air plasma did not effect on Paschen minimum which is 0.5 without dust and with Fe3O4 dusty grains. The effect of Fe3O4 dust particles on plasma parameters can be notice in direct current system in glow discharge region. The plasma parameters which were studied in this work represent plasma potential, floating potential,electron saturation current, temperature of the electron, the density of the (electron, ion), and Debye length. The measurements of parameters are taken by four cylindrical probes which diagnosed at distance 4cm from the diameter of the cathode in Paschen minimum at pressure 0.5 Torr. The diameter profiles of plasma parameters in the present of dust are non- uniform. Plasma potential and the floating potential of probe becomes more negatively when the dust immersed into plasma region. The electron density increases in the present of dust particle which lead to decrease the electron temperature and Debye length. The behavior of those parameters shows the discharge current and discharge voltage increases without dust while the discharge current and voltage decreases when Fe3O4 dust particles embedded.